2017
DOI: 10.2147/iprp.s125085
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of intravenous medication administration errors: a cross-sectional study

Abstract: BackgroundIntravenous medication administration errors (MAEs) may be accompanied by avoidable undesirable effects, which might result in clinical complications.ObjectiveThe aim of the study was to determine the prevalence of MAEs and to identify the factors associated with such errors.MethodsA hospital-based cross-sectional study was conducted from March to April 2015. Data were collected by direct observation using a pretested data collection tool. Simple random sampling was used, and bivariate logistic regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 17 publications
0
32
0
2
Order By: Relevance
“…Omitted drug error: is failure to administer a prescribed medication, patient error: when a medication of one patient is wrongly given to another patient, dose error: when prescribed quantity is not administered, medication error: when another medication is administered to the patient other than the prescribed, time error: when there is a difference of greater or less than 30 min between the ordered time and administered time, unauthorized drug error: medication administered was not authorized by the prescriber, technique error: the nurse performs less than 50% among the procedure put at the technique competency checklist for medication administration, route error: when medication is administrated in different route other than the ordered actual route, documentation error: When medication that is administered to the patient is not documented in medication administration record sheet. [17][18][19][20]36,37 This review targets all nurses in Ethiopia. Studies, in which participants were drawn from overall health care professionals, were excluded; unless the studies were separately documented for nurses.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Omitted drug error: is failure to administer a prescribed medication, patient error: when a medication of one patient is wrongly given to another patient, dose error: when prescribed quantity is not administered, medication error: when another medication is administered to the patient other than the prescribed, time error: when there is a difference of greater or less than 30 min between the ordered time and administered time, unauthorized drug error: medication administered was not authorized by the prescriber, technique error: the nurse performs less than 50% among the procedure put at the technique competency checklist for medication administration, route error: when medication is administrated in different route other than the ordered actual route, documentation error: When medication that is administered to the patient is not documented in medication administration record sheet. [17][18][19][20]36,37 This review targets all nurses in Ethiopia. Studies, in which participants were drawn from overall health care professionals, were excluded; unless the studies were separately documented for nurses.…”
Section: Methodsmentioning
confidence: 99%
“…20,37 Type and magnitude of MAEs Regarding the types of MAEs, though the proportion of MAEs is varied for each type of error based on the number of rights used as a reference 26,27 definitions 46 and phases of medication administration process; [11][12][13] in this study, around thirteen different types of MAEs were identified such as: wrong route, wrong time, wrong patient, wrong dose, wrong drug, error of omission, wrong rate, documentation errors, duration error, technical error, unauthorized and without hand washing/change glove. [17][18][19][20]24,36,37 In each included study, five 18 up to eight 37 different types of MAEs were identified; though, one study reported only the overall result. 45 The most frequently reported type of MAEs were wrong time and wrong dose errors (n=6.7).…”
Section: Figure 1 Flowchart Of the Studymentioning
confidence: 99%
See 3 more Smart Citations